Incidental venous thromboembolism in ambulatory cancer patients receiving chemotherapy - Nisio, Marcello Di; Ferrante, Noemi; Tursi, Michele De; Iacobelli, Stefano; Cuccurullo, Franco; Büller, Harry R.; Feragalli, Beatrice; Porreca, Ettore (Thrombosis and Haemostasis, 2010)
While the association between cancer and symptomatic venous thromboembolism (VTE) is well established, the incidence and risk factors for incidental VTE in cancer patients remain unclear. The medical records of 1,921 consecutive cancer patients starting chemotherapy from January 2003 up to March 2009 were identified. Patients with a positive history of VTE were excluded. Pre-existing signs of VTE, kind and stage of malignancy, first and subsequent lines of chemotherapy, and all follow-up computed tomography (CT) scans were analysed. The primary outcome was incidental VTE. Overall, there were 101 (5.3%) VTE, 62 (3.2%) incidental and 39 (2.0%) symptomatic during a median of eight months (range 3–72). The incidence on CT scans was 0.58% (95%CI: 0.44–0.74). Incidental VTE included 24 pulmonary embolism, 28 deep venous thrombosis of the extremities, and 10 thromboses of the cava or splanchnic veins. Half of the incidental VTE occurred in the first 3–6 months of chemotherapy with a relatively higher incidence in gyneco-logical and lung cancers. The presence of metastases, high leukocyte count, and platin-based chemotherapy increased the risk up to threefold. All patients with incidental VTE regardless the location received half to full therapeutic doses of low-molecular-weight heparin for a minimum of three months. In summary, incidental VTE is a relative common finding in patients with solid tumours, especially in the first months of chemotherapy. Further research is needed to understand the natural history of incidental thrombosis in order to develop adequate management guidelines.
Keywords: Cancer; venous thrombosis; chemotherapy